The Stuff of Soil: Belowground Agency in the Making of Future Climates. Issue 1 (1st March 2019) - Granjou, Céline; Salazar, Juan Francisco
Abstract : Despite soil's vital ecological importance, its significance as a belowground tridimensional living world remains under-theorized in social and cultural research. Drawing on the reading of scientific literature and a series of interviews with scientists working at the juncture of soil and climate research, this article pursues a picture that highlights soil's capacities to shape future climates, including by fostering major planetary tipping points; we elaborate on the cultural and ethical significance of that picture for opening up alternative stories in which agency and change are not human-only prerogatives. We develop a critical stance on the growing expectations of storing more carbon into soils and argue for a better consideration of the situated, heterogeneous, and volatile dynamics of carbon within soils. We eventually call for more responsible ways of thinking about, and caring for, the myriad conglomerates of living, decaying, and dead matter that basically make up the stuff of soil.